Komunikasi Politik di Era Media Sosial - Faridhian Anshari (Jurnal Komunikasi)
The development of communication technology has penetrated the lives of human beings. One form of communication is the development of new media technologies who gave birth to social media. Political world is also not free from the influence of new media and social media. Social media are like two sides of a coin for political actors. On the one hand, the success by using social media is getting positive support. But on the other hand failure by using social media is the risk by damaging the image. This paper discusses the challenges and opportunities of social media on political actors. Exposure to the use of social media in political communication becomes the first part of this paper. The second section discusses the challenges faced by political actors in the 2.0 era. The third section gives an offer opportunity for political actors in the utilization of social media. There is also the fourth and final section is a conclusion that contains what should be done by political actors to minimize the risks and maximize the opportunities offered by social media.